1984
DOI: 10.1182/blood.v64.4.907.bloodjournal644907
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a fast-acting inhibitor of plasminogen activators in human plasma

Abstract: This report describes a plasmatic, fast-acting, specific inhibitor (antiactivator) of tissue-type plasminogen activator (t-PA) and urokinase (UK). After addition of t-PA to human plasma, biexponential decay of activity occurred. The initial rapid inhibition of t-PA activity (half-life of approximately one minute) was correlated with the formation of a complex of a molecular weight of 110,000, suggesting a molecular weight in the order of 40,000 for the antiactivator. Diisopropylfluorophosphate (DFP)-inactivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
118
1
2

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(131 citation statements)
references
References 36 publications
10
118
1
2
Order By: Relevance
“…The activity of this activator is highly stimulated by fibrin (Thorsen et al, 1972) and specifically inhibited by PA inhibitors (Sprengers & Kluft, 1987). The fast-acting inhibitor of endothelial-cell origin (Dosne et al, 1978;Loskutoff et al, 1983) present in plasma (Thorsen Kruithof et al, 1984;Wiman et al, 1984;Verheijen et al, 1984), PAI-1, reacts with both single-chain t-PA (sc-t-PA) and two-chain t-PA (tc-t-PA) and with the twochain urinary-type plasminogen activator (tc-u-PA, EC 3.4.21.31) with a second-order rate constant of above 107m-l s-W. PAI-i forms SDS-stable complexes with these activators (Levin, 1983;Philips et al, 1984). The inhibitor of placental origin (Kawano et al, 1968;Astedt et al, 1985), PAI-2, also found in plasma during pregnancy (Lecander et al, 1984), can inhibit tc-t-PA and tc-u-PA with a second-order rate constant of 106 M-1 s-'.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of this activator is highly stimulated by fibrin (Thorsen et al, 1972) and specifically inhibited by PA inhibitors (Sprengers & Kluft, 1987). The fast-acting inhibitor of endothelial-cell origin (Dosne et al, 1978;Loskutoff et al, 1983) present in plasma (Thorsen Kruithof et al, 1984;Wiman et al, 1984;Verheijen et al, 1984), PAI-1, reacts with both single-chain t-PA (sc-t-PA) and two-chain t-PA (tc-t-PA) and with the twochain urinary-type plasminogen activator (tc-u-PA, EC 3.4.21.31) with a second-order rate constant of above 107m-l s-W. PAI-i forms SDS-stable complexes with these activators (Levin, 1983;Philips et al, 1984). The inhibitor of placental origin (Kawano et al, 1968;Astedt et al, 1985), PAI-2, also found in plasma during pregnancy (Lecander et al, 1984), can inhibit tc-t-PA and tc-u-PA with a second-order rate constant of 106 M-1 s-'.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the fibrinolysis system is triggered by types of plasminogen activators; it is mainly by plasminogen activator inhibitor.-1 ' ~ ~'). inhibits both tissue-type plasminogen activator and urokinase-type plasminogen activator (uPA) (2)(3)(4). activator inhibitor-1 is therefore añ important regulator of extracellular proteolysis and fibrinnolysis that plays important role in turnover of the extracellular matrix.…”
mentioning
confidence: 99%
“…latent ~'~rm~ it can be also converted its active form after treatment with denaturants (5). plasma, PAI-1 forms stable stoichiometric complexes with tPA (6). As PAI-I levels rise in plasma, jthe fraction of tPA in the active form falls while the 'issue-type activator/plasminogen activator inhibitor-I (tPA/PAI-1) complex levels rise (7,8).…”
mentioning
confidence: 99%
“…The system is regulated at many different levels, of which inactivation of tissue plasminogen activator (tPA) by plasminogen-activator inhibitor 1 (PAI-1) is an important part [1]. PAI-1 exists in plasma [2,3], and elevated levels seems to be connected with thrombotic disease [4,5]. It is a glycoprotein with an Mr of about 50000, consisting of 379 amino acids, as revealed from its cDNA sequences [6,7].…”
Section: Introductionmentioning
confidence: 99%